(untitled) (International journal of medical sciences, 2026)
Background: Essential hypertension is a widespread cardiovascular disorder. The hyperactivation of the sympathoadrenal system (SAS) is considered one of the primary pathogenetic mechanisms leading to the elevation of blood pressure and subsequent target organ damage. Objective: To evaluate the functional state of the sympathoadrenal system by assessing catecholamine levels in patients diagnosed with essential hypertension. Methods: The study included 78 patients with Stage II essential hypertension and a control group of 20 healthy individuals. The functional state of the SAS was evaluated by measuring plasma levels of epinephrine (adrenaline) and norepinephrine (noradrenaline) using high-performance liquid chromatography. Hemodynamic parameters, including systolic and diastolic blood pressure, and heart rate, were also recorded. Results: Patients with hypertension exhibited a significant increase in SAS activity. Plasma norepinephrine levels were significantly higher in the hypertensive group (412.5 ± 35.2 pg/mL) compared to the control group (265.4 ± 22.8 pg/mL, p < 0.05), indicating elevated sympathetic nervous system tone. Epinephrine levels were also increased (74.3 ± 8.1 pg/mL vs. 42.1 ± 5.4 pg/mL, p < 0.05). A strong positive correlation was found between plasma norepinephrine levels and both systolic blood pressure and heart rate. Conclusion: Essential hypertension is characterized by marked hyperactivation of the sympathoadrenal system. This sustained sympathetic overdrive contributes to the maintenance of high blood pressure and highlights the necessity of incorporating sympatholytic or neuromodulatory agents in the comprehensive management of these patients.